SIL (Neo Scientific Peer Reviewed Journal, 2026)
This article explores the properties, applications, and significance of silicon (Si) in various fields, including electronics, renewable energy, and materials science. It highlights recent advancements and future trends, emphasizing silicon's pivotal role in technological innovation and sustainability.